2019
DOI: 10.3389/fonc.2019.00584
|View full text |Cite
|
Sign up to set email alerts
|

A Simple-to-Use Nomogram for Predicting the Survival of Early Hepatocellular Carcinoma Patients

Abstract: Objective: This study aimed to develop and validate a simple-to-use nomogram for early hepatocellular carcinoma (HCC) patients undergoing a preoperative consultation and doctors conducting a postoperative evaluation. Methods: A total of 2,225 HCC patients confirmed with stage I or II were selected from the Surveillance, Epidemiology, and End Results database between January 2010 and December 2015. The patients were randomly divided into two groups: a training group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 47 publications
2
35
1
Order By: Relevance
“…Conditional backward selection was used to select the final variables for constructing the models. This method is frequently used to identify predictive factors for prognosis in clinical research [ 13 ]. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Conditional backward selection was used to select the final variables for constructing the models. This method is frequently used to identify predictive factors for prognosis in clinical research [ 13 ]. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional staging systems, such as the American Joint Committee on Cancer 8th edition (AJCC8th) and the Barcelona Clinic Liver Cancer (BCLC) staging systems, cannot satisfactorily predict postoperative prognosis ( 3 ). As a new clinical prognostic model, nomograms have been explored in several carcinomas ( 4 6 ). However, scholars have not reached a unified standard or consensus for a clinical prognosis model of an HCC nomogram.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a nomogram might be used as a dependable instrument for predicting patients’ survival outcomes and supporting decisions with regard to surgery, surveillance, and adjuvant treatments. Recently, some researchers have reported that the nomogram scoring system has an exceptional capability in predicting prognosis [13, 14]. However, most nomograms used to predict the prognosis of patients with colon cancer, of which the sample size used for development was limited, required a combination of molecular biology tests, which increased the economic burden, time and cost for the patient.…”
Section: Introductionmentioning
confidence: 99%